Analisis Korelasi Faktor Perilaku Konsumen terhadap Keputusan Penggunaan Teknologi Komunikasi Voip - Budi Yulianto (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The advancement of communication technology that is combined with computer and the Internet brings Internet Telephony or VoIP (Voice over Internet Protocol). Through VoIP technology, the cost of telecommunications in particular for international direct dialing (IDD) can be reduced. This research analyzes the growth rate of VoIP users, the correlation of the consumer behavior towards using VoIP, and cost comparisons of using telecommunication services between VoIP and other operators. This research is using descriptive analysis method to describe researched object through sampling data collection for hypothesis testing. This research will lead to the conclusion that the use of VoIP for international area will be more advantageous than the use of other operators of GSM (Global System for Mobile), CDMA (Code Division Multiple Access), or the PSTN (Public Switched Telephone Network).